Bioaccessibility and Functional Food Potential of Equisetum telmateia Ehrh. Against Diabetes-Induced Kidney Disorders - Timur Hakan Barak; İnci Kurt-Celep; Engin Celep (Foods)
Various species from the genus Equisetum are recorded as food and folk medicine against both kidney complications and diabetes. Equisetum telmateia Ehrh. is documented as a folk remedy in Türkiye against several kidney disorders. This study was designed to evaluate the possible protective mechanisms of E. telmateia EtOH extract (ETE) against kidney disorders and diabetes through different routes, such as the prevention of ROS formation, inhibitory potential against various DM-related enzymes, and a reduction in the amount of the mediators leading to disorders in both systems at the cellular level. The objective was to achieve advanced precision for in vitro results while considering the effect of GIS on oral consumption. Both phytochemical and bioactivity studies were conducted before and after simulated digestion. The results showed that ETE is a rich source of flavonoids and phenolic acids. In addition, it has significant antioxidant and enzyme inhibitory potential. Treatment also yielded promising results at the cellular level for both antioxidative and inhibitor proteins, which may play a role in the pathogenesis of kidney disorders and diabetes. Following the in vitro digestion procedure, both the number of phytochemical ingredients and bioactivity parameters showed a considerable decreasing trend; however, the results are still significant enough to justify the traditional utilization of the genus Equisetum. This investigation demonstrated that ETE has noteworthy potential as a functional food for protection against diabetic kidney disease.